Penggunaan Kartu Bergambar Angka Dalam Pembelajaran Bahasa Arab Anak Usia Dini - Hamidah; Mabruri (E-JURNAL AKSIOMA AL-ASAS, 2025)
The purpose of this study is to determine the use of picture cards in recognizing Arabic numbers for early childhood. This study uses a literature study method, the data collection technique is by analyzing books, journals and articles that are still related to the research topic. The results of this literature review are the use of Arabic picture cards for early childhood is considered very relevant. By using picture cards, children are more enthusiastic in learning Arabic, the Arabic learning process is more enjoyable, children are easier to catch and understand each lesson to recognize numbers in Arabic. In addition, picture cards are an effective learning tool to improve the understanding of Arabic vocabulary in early childhood. Picture cards can make it easier for children to recognize between pictures and vocabulary, and encourage an active and effective learning process through singing together by showing the picture cards to children in turns, the use of picture cards is highly recommended in Arabic language learning activities in early childhood education institutions to make it easier for teachers and students to achieve these learning objectives. Keywords: Learning Media, Picture Number Cards, Arabic for Early Childhood